Postcranial osteology of the neotype specimen of Massospondylus carinatus Owen, 1854 (Dinosauria: Sauropodomorpha) from the upper Elliot formation of South Africa - Barrett, Paul M.; Chapelle, Kimberley E.J.; Staunton, Casey K.; Botha, Jennifer; Choiniere, Jonah N. (Evolutionary Studies Institute, 2019)
Massospondylus carinatus Owen, 1854, from the earliest Jurassic upper Elliot Formation of South Africa, was one of the first dinosaurs to be described from Gondwana. It has been incorporated into numerous phylogenetic, palaeobiological and biostratigraphic analyses, is often viewed as an exemplar for understanding sauropodomorph anatomy and is a key taxon in studies of early dinosaur evolution. Since its initial description, numerous specimens have been referred to this species, ranging from isolated postcranial elements to complete skeletons with three-dimensional skulls. In addition,M. carinatus has been identified in areas outside of the main Karoo Basin. Surprisingly, however, there have been few attempts to define the taxon rigorously, so that the basis for many of these referrals is weak, undermining the utility of this abundant material. Here, we provide the first detailed postcranial description of the neotype specimen ofM. carinatus, use it as a basis for diagnosing the species on the basis of cranial, axial and appendicular characters, demonstrate that it represents an adult individual on the basis of osteohistology, and discuss ways in which these data can assist in providing a better understanding of Karoo-aged African dinosaur faunas.
Keywords: Massospondylidae; postcranial anatomy; osteohistology; taxonomy